Rencana Umum Energi Daerah dalam Perspektif Implementasi Filosofi Tri Hita Karana dan Visi Pemerintah Provinsi Bali - Ni Putu Tirka Widanti (Jurnal Kajian Bali (Journal of Bali Studies), 2021)
This study aimed at reviewing and providing perspective concerning how the Balinese local genius of Tri Hita Karana and the vision of Bali could be implemented in the Regional Energy General Plan (RUED) of Bali Province. This study used the descriptive qualitative method with causal inference concluding technique. The data were collected from the process of drafting, consulting, discussing, and stipulating Regional Regulation No. 9 of 2020 concerning RUED of Bali Province 2020-2050. The finding showed that there is a significant and strong relationship of the implementation of Tri Hita Karana and Bali Vision on the RUED of Bali Province to maintain the balance and harmony among the humans, nature, and Balinese culture as the primary tourist destination in Indonesia which highly depending on the attractiveness of its culture and natural environment. There are new things in terms of its management strategy as the evaluation result of some pilot projects in implementing new and renewable energy in Bali Province.